Islamic banking and sectoral economic growth: Evidence from Indonesia - Fauzul Hanif Noor Athief; Sulistya Rusgianto; Sri Herianingrum; Muhammad Iqbal Surya Pratikto; ‘Azizah Fathma (Banks and Bank Systems)
Grounded in the financial development-economic growth nexus, this study aims to explore the role of Islamic banking in shaping sectoral economic growth in Indonesia. Specifically, it examines the effects of Islamic bank financing (IBF) and non-performing financing (NPF) on sectoral GDP to identify variations in their impact across key sectors. Using quarterly time-series data from 2011Q1 to 2024Q3, the Autoregressive Distributed Lag (ARDL) model was employed to examine short-term and long-term relationships. Findings reveal sector-specific variations in the effects of IBF and NPF. In the long run, IBF has a significant positive impact on the education sector (13.13), health (3.95), accommodation (3.30), and construction (2.73). In contrast, IBF shows a significantly negative effect in agriculture (–87.65), fisheries (–21.49), and real estate (–5.04). NPF generally shows negative effects on sectoral GDP, particularly in accommodation (–136.67), education (–1122.11), and manufacturing (–215.75), while showing unexpected positive effects in health (234.46) and real estate (7.50). Short-term analysis highlights both positive and negative effects of IBF and NPF, with notable variations across sectors where IBF boosts GDP in health (2.73) and sales (3.04), but negatively impacts manufacturing (–2.38) and fisheries (–8.04); NPF has a short-term negative effect in accommodation (–90.38) and education (–433.93), with lagged positive adjustments in some sectors. Lagged effects of NPF suggest delayed financial adjustments and sector-specific recovery patterns. These findings provide sector-specific empirical insights that can inform the design of more effective Islamic financial policies and targeted interventions to support inclusive and sustainable economic growth.